Early Adalimumab and Anti‐Adalimumab Antibody Levels for Prediction of Primary Nonresponse in Ankylosing Spondylitis Patients. Issue 3 (13th February 2020) - Ding, Xiaoliang; Zhu, Ruifang; Wu, Jian; Xue, Ling; Gu, Meihua; Miao, Liyan
Abstract : This study aimed at exploring the concentration‐effect relationship of adalimumab and early adalimumab and anti‐adalimumab antibody (AAA) levels in predicting primary nonresponse in a real‐world pilot cohort of patients with ankylosing spondylitis. Thirty‐one patients were included. The Ankylosing Spondylitis Disease Activity Score improved with increasing adalimumab trough level at week 12 and reached a major improvement with levels between 8 and 12 μg/mL. Moreover, weeks 4 and 2 adalimumab levels below 4.28 and 3.37 μg/mL were predictive of primary nonresponse (area under the curve (AUC) = 0.89, 0.88; P  = 0.0003, P  = 0.034, respectively). Week 4 AAA signal‐to‐noise levels were significantly higher among primary nonresponders, and the cutoff for primary nonresponse prediction was above 5.31 (AUC = 0.81; P  = 0.004). Adalimumab trough levels in a range of 8–12 μg/mL are optimum to reach major improvement, and lower adalimumab with higher AAA levels at the early stage (week 4) predict primary nonresponse by supporting proactive monitoring to optimize adalimumab therapy.